Management of the complications of BPH/BOO - Mark J Speakman; Xi Cheng (Indian Journal of Urology, 2014)
Most men will develop histological BPH if they live long enough. Approximately, half will develop benign prostatic enlargement (BPE) and about half of these will get BOO with high bladder pressures and low flow, this in turn leads to detrusor wall hypertrophy. Many of these men will only have lower urinary tract symptoms (LUTS) but a significant number will also suffer the other complications of BPH. These include urinary retention (acute and chronic), haematuria, urinary tract infection, bladder stones, bladder wall damage, renal dysfunction, incontinence and erectile dysfunction. Recognition of the complications of BPH/BOO early allows more effective management of these complications. This is particularly important for the more serious urinary infections and also for high-pressure chronic retention (HPCR). Complications of LUTS/BPH are very rare in clinical trials because of their strict inclusion and exclusion criteria but are more common in real life practice.